Feed the dogs: The case of humanitarian communication in social media - Knudsen, Gry Høngsmark; Bajde, Domen (MedieKultur: Journal of media and communication research, 2016)
In this paper we address the interplay between networked media and humanitarian communication through the lens of meditization theory in order to forward a more balanced understanding of networked humanitarianism. We analyze a case of humanitarian communication that travelled Facebook in unpredictable ways and demonstrate the breakdown between sender and receiver positions. The case shows how communicative practices are challenged and how humanitarian organizations are destabilized in a new and unpredictable communication environment. We argue that in order to deepen the critical perspective on networked humanitarian communication, it is important to better understand how the institutional logic of humanitarianism changes when mediatized through networked media. Further, we suggest that a broader consideration of media amalgamation enables a critical discussion of networked media influence humanitarianism.